Determination of gonad maturation stages morphologically and the reproduction period in Sillago suezensis (Forsskal, 1775) (Sillaginidae) migratory from the Red Sea in the marine waters of Latakia Governorate (Latakia University Journal -Biological Sciences Series, 2024)
This research was carried out on /338/ individuals of fish Sillago suezensis from the migratory in Syrian coast, during the period between 23/6/2022 and 23/6/2023, different means used locally private fishing nets, especially the gill nets, at depths ranging from 3 m to 50 m.The TL (total length) of the samples varies between (10 -20.6) cm with an average TL is (15.01± 2.1) cm for females and (8-20.3) cm with an average TL is (15.07± 1.97) for males. The TW (total weight) of the specimens ranges between (5.84-69.98) g with an average value of (27.77 ±11.55) g for females and (2.84 ±67.71) g with an average value of (27.15 ±10.55) g for males.The duration of reproduction was determined by studying the GSI%. The GSI% was highest in June (4.58 ± 2) for males and in September (6.22 ± 2.77) for females. The breeding season for this species extends from May to November.The stages of development of gonad maturity conformed morphologically corresponded to the six-sided scale of gonad maturity.